Exposure of protected areas in Central America to extreme weather events - González-Trujillo, Juan David (Conservation biology : the journal of the Society for Conservation Biology, 2024)
© 2024 The Authors. Conservation Biology published by Wiley Periodicals LLC on behalf of Society for Conservation Biology.